PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP PENDAPATAN EKONOMI - Nadya Rahma; Putri Indah Lestari; Sucy Rahmadia; Nahdatul Zikri; M.Taufiq Al Aziz; Beni Bastian; Ansofino Ansofino (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of Regional Original Revenue (PAD) and Balancing Funds (DP) on Economic Growth in West Sumatra Province. The data used are panel data from 12 regencies and 7 cities during the period 2022–2024 obtained from the Central Statistics Agency (BPS). The analytical method used is panel data regression with the Panel Least Squares approach. The results show that Regional Original Revenue has a positive but insignificant effect on economic growth, with a coefficient value of 0.000817 and a probability value of 0.0625. Likewise, Balancing Funds have a positive but insignificant effect on economic growth with a coefficient value of 0.000378 and a probability value of 0.7369. Simultaneously, PAD and DP do not significantly affect economic growth, as indicated by the Prob(F-statistic) value of 0.1706. The coefficient of determination (R-squared) is 0.063, indicating that only 6.3% of the variation in economic growth can be explained by PAD and DP, while the remaining 93.7% is influenced by other factors outside the model. These findings indicate that economic growth in West Sumatra is not solely determined by regional revenue and balancing funds but is also influenced by other economic factors.